Rural Education in a Decolonial Turn: the Community-Time Experience at the Fluminense Federal University (UFF) - Francisca Marli Rodrigues de Andrade; Letícia Pereira Mendes Nogueira; Lucas do Couto Neves; Marcela Pereira Mendes Rodrigues (Universidade Federal do Norte do Tocantins, 2020)
Rural Education in Brazil, in five decades, has been constructing an educational practice that values and includes the subjects, the lores and the social experiences of the countryside; that is, the Pedagogy of Alternation. In the university context, Alternance reorganizes the spaces of learning in Community-Time (CT) and School-Time (ST) and, therefore, proposes questions to the logics of colonization/modernity of knowledge, imposed on Latin America. In this reorganization, the present research has as objective: to know the process of construction of Community-Time, implemented in the Interdisciplinary Degree in Rural Education (UFF), to identify decolonial pedagogical elements that potentiate the formation of educators in the rural zone. Methodologically, we adopted a qualitative-oriented research, which is inscribed in the interpretative approach. To collect data, we performed semi-structured interviews with 5 teachers and 12 students; documentary analysis of the 12 projects of the Thematic Fields of Community-Time. The main results point to the importance of Community-Time in of rural educators' formation as well as in the processes of transformation of reality. Likewise, the power of action-reflection of the Community-Time in encouraging actions to strengthen citizenship and the organization of emancipatory struggles.